2013
DOI: 10.1007/s00330-013-2956-1
|View full text |Cite
|
Sign up to set email alerts
|

Locally advanced rectal cancer: is diffusion weighted MRI helpful for the identification of complete responders (ypT0N0) after neoadjuvant chemoradiation therapy?

Abstract: Adding DWI to T2-MRI improves consistency between readers and has potential to improve readers' accuracy dependent on his/her experience. DWI could be of additional value, particularly in ruling out CR (high NPV), but considering the sub-optimal PPV one should be cautious about relying solely on MRI for the clinical decision to offer a wait-and-see strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 25 publications
5
51
2
2
Order By: Relevance
“…Four studies have compared the accuracy of DWI and standard MRI in predicting the response to nCRT. Three of the four studies found that DWI improved the interobserver reliability of different radiologists in assessing pCR but this was not statistically significant for all the radiologists . In all studies, the accuracy of DWI was insufficient to change clinical practice .…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Four studies have compared the accuracy of DWI and standard MRI in predicting the response to nCRT. Three of the four studies found that DWI improved the interobserver reliability of different radiologists in assessing pCR but this was not statistically significant for all the radiologists . In all studies, the accuracy of DWI was insufficient to change clinical practice .…”
Section: Resultsmentioning
confidence: 85%
“…Three of the four studies found that DWI improved the interobserver reliability of different radiologists in assessing pCR but this was not statistically significant for all the radiologists [81,82,93,94]. In all studies, the accuracy of DWI was insufficient to change clinical practice [81,82,94,95]. One study noted that the high negative predictive value might be of value in excluding pCR, but the positive predictive value was poor [94].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 96%
“…Four articles demonstrate that late qualitative DWI assessment can predict pCR with a pooled specificity of 94% and an overall accuracy of 87%, thereby outperforming quantitative DWI measurements [30,[36][37][38].…”
Section: Resultsmentioning
confidence: 97%
“…38 MRI achieved a much higher level of agreement between pre-operative staging and histologic assessment compared to digital rectal examination and EUS, 39 although a low positive predictive value for absence of pCR after a MRI T2 weighted was reported. 40 Unfortunately, the excellent anatomical data provided by MRI cannot rule out small clusters of cancer after CRT. In our series, five patients presented isolated LR, and we proposed resection to all of them.…”
Section: Discussionmentioning
confidence: 99%